A novel Eulerian approach for modelling cyanobacteria movement: Thin layer formation and recurrent risk to drinking water intakes. (15th December 2017) - Ndong, Mouhamed; Bird, David; Nguyen Quang, Tri; Kahawita, René; Hamilton, David; de Boutray, Marie Laure; Prévost, Michèle; Dorner, Sarah
Abstract: Toxic cyanobacteria (CB) blooms are being reported in an increasing number of water bodies worldwide. As drinking water (DW) treatment can be disrupted by CB, in addition to long term management plans, short term operational decision-making tools are needed that enable an understanding of the temporal variability of CB movement in relation to drinking water intakes. In this paper, we propose a novel conservative model based on a Eulerian framework and compare results with data from CB blooms in Missisquoi Bay (Québec, Canada). The hydrodynamic model considered the effects of wind and light intensity, demonstrated that current understanding of cell buoyancy in relation to light intensity in full-scale systems is incomplete and some factors are yet to be fully characterized. Factors affecting CB buoyancy play a major role in the formation of a thin surface layer that could be of ecological importance with regards to cell concentrations and toxin production. Depending on velocities, wind contributes either to the accumulation or to the dispersion of CB. Lake recirculation effects have a tendency to create zones of low CB concentrations in a water body. Monitoring efforts and future research should focus on short-term variations of CB throughout the water column and the characterization of factors other than light intensity that affect cell buoyancy. These factors are critical for understanding the risk of breakthrough into treatment plants as well as the formation of surface scums and subsequent toxin production. Graphical abstract: Highlights: We propose a novel conservative model based on an Eulerian framework. The risks associated with Cyanobacteria blooms could be cyclic. Lake recirculation effects have a tendency to create zones of low CB concentrations.